Assessing the sustainability of advanced and developing countries: a different perspective - Trusina, Inese; Jermolajeva, Elita (Business, Management and Economics Engineering, 2024)
Purpose – The research aim of the article is the analysis of advanced/developed and developing countries in the context of sustainable development, using invariant coordinate system in energy units, as well as the impact of structural changes in the economy affect the possibility of transition to sustainable development and creation post-industrial society. Research methodology – In order to achieve the aim were applied the method of socio-economic systems power changes analyzing in the frame of structural economic Kaldor model of GDP and the energy flows models. Finding – The advanced countries have seen a trend of “zero growth” and a decrease in useful energy production in the last 10 years. These countries have high labor productivity, technological level and diminishing potential for sustainable development. China is in the stage of “growth and development” and has great potential. Data calculated by the authors of the article correlates with the findings of the Kaldor model. Research limitation – The initial interpretation of the calculated data of France, Germany, Japan, USA, European Union and China was made. Countries have been analyzed in the period from 1990 to 2019. The data of the Central Statistical Office of EU and the World Bank were used. Practical implications – The results of the study can be used to further planning and design of transition to sustainable development for advanced and developing countries. Originality/Value – within the framework of the approach, an invariant coordinates system in energy units is proposed and the main parameters for assessing the potential of growth and sustainable development for advanced countries were formed.